2021
DOI: 10.1186/s12872-021-01963-1
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 (COVID-19) and QTc prolongation

Abstract: Introduction The cause-and-effect relationship of QTc prolongation in Coronavirus disease 2019 (COVID-19) patients has not been studied well. Objective We attempt to better understand the relationship of QTc prolongation in COVID-19 patients in this study. Methods This is a retrospective, hospital-based, observational study. All patients with normal baseline QTc interval who were hospitalized with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
1
19
2
2
Order By: Relevance
“…after falling ill with COVID-19 compared to before [41]. Previously reported QT intervals ranges from a mean of 443-450 ms [40][41][42][43], which is somewhat longer than the mean of 440 ms reported in this study.…”
Section: Plos Onecontrasting
confidence: 68%
See 2 more Smart Citations
“…after falling ill with COVID-19 compared to before [41]. Previously reported QT intervals ranges from a mean of 443-450 ms [40][41][42][43], which is somewhat longer than the mean of 440 ms reported in this study.…”
Section: Plos Onecontrasting
confidence: 68%
“…In their cohort, patients were older (74 vs 61 years) and had higher over-all mortality (46% vs 28%) compared to our study, which may account for some of the differences between our study and theirs. Previous studies reported longer QT interval in patients with COVID-19 compared to patients without COVID-19 [ 40 ] and QT prolongation after falling ill with COVID-19 compared to before [ 41 ]. Previously reported QT intervals ranges from a mean of 443–450 ms [ 40 43 ], which is somewhat longer than the mean of 440 ms reported in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With prolonged QTc, the frequency of ventricular arrhythmias and mortality rate increases especially in cardiovascular diseases. Prolonged QTc duration has been reported to be associated with prognosis in COVID-19 infection (14,15). In our study, the QTc duration was found to be significantly longer in the "deceased patient" group.…”
Section: Discussionsupporting
confidence: 50%
“…It has been reported that QTc of >455 ms in males and >465 ms in females are predictors of mortality, 8) and the absence of QT prolongation was associated with a good prognosis. 9) In contrast, Changal et al 10) reported that QTc prolongation was not associated with increased ventricular arrhythmias or mortality in multivariate analysis. Because QT prolongation is in part a result of myocardial damage, it cannot be discriminated independently.…”
mentioning
confidence: 94%